2021
DOI: 10.1186/s13071-021-04580-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the gut microbiota in mothers and children with chronic Trichuris trichiura infection in Pemba Island, Tanzania

Abstract: Background Soil-transmitted helminthiases are important neglected tropical diseases that result in a notably high number of disability-adjusted life years worldwide. Characterizing the interactions between the human intestinal microbiome and helminths is of interest in the development of alternative treatments that do not rely on chemotherapeutics and do not lead to drug resistance. Methods We recruited and obtained fecal samples from 32 pairs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…In this metagenomic study, we found that intestinal helminth infection status was associated with higher species richness, which was consistent with our previous findings and others conducted using 16s rRNA sequencing [10, 12, 13, 17, 30, 32]. However, we did not find a significant difference at Pre and Post deworming, which could be because of smaller sample size and could also be confounded by the effects of albendazole.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this metagenomic study, we found that intestinal helminth infection status was associated with higher species richness, which was consistent with our previous findings and others conducted using 16s rRNA sequencing [10, 12, 13, 17, 30, 32]. However, we did not find a significant difference at Pre and Post deworming, which could be because of smaller sample size and could also be confounded by the effects of albendazole.…”
Section: Discussionsupporting
confidence: 91%
“…These divergent conclusions could be attributed to different confounders from different geographical locations (e.g. Malaysia [7, 13], Indonesia [10], Liberia [10], Tanzania [12], Western Kenya [11] and Ecuador [14]), different prevalence of helminth species (e.g. Trichuris sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the microbiota during helminth infection is becoming increasingly recognized, and is also the start of an exciting and crucial area of parasitological research. Microbial changes have been reported for multiple intestinal helminths including infections with Ascaris lumbricoides (Ramírez-Carrillo et al ., 2020 ), H. polygyrus (Walk et al ., 2010 ; Kreisinger et al , 2015 ), Necator americanus (hookworm; Cantacessi et al ., 2014 ) and of interest for this review T. trichiura (Lee et al ., 2014 ; Chen et al ., 2021 ) and T. muris (Holm et al ., 2015 ; Houlden et al ., 2015 ; Schachter et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the conflicting data in human field studies, and their comparison to mouse models are due to the fact that infected individuals are rarely exposed to a single, low-dose helminth infection but rather continuous re-occurring infection by the same or multiple parasites. A recent study in Tanzania, was one of the first to identify a reduction in the abundance of gut bacteria: Bacteroidetes, Proteobacteria and Actinobacteria associated with a cohort of women and children solely infected with T. trichuria (Chen et al, 2021); which is similar to the microbial changes reported in mouse studies (Holm et al, 2015;Houlden et al, 2015). Parallels between human and mouse studies were further addressed by identifying bacterial taxa that increased in both T. trichuria-only infected Indonesian individuals and T. muris-infected mice, these genera included Bacteroides, Collinsella, Subdoligranulum, Escherichia/Shigella, Prevetoella and Streptococcus (Rosa et al, 2021).…”
Section: Reoccurring Trichuriasis and The Gut Microbiotamentioning
confidence: 99%